Benchmarking progress in tackling the challenges of intellectual property, and access to medicines in developing countries - Musungu Sisule F (The World Health Organization, 2006)
The impact of intellectual property protection in the pharmaceutical sector on developing countries has been a central issue in the fierce debate during the past 10 years in a number of international fora, particularly the World Trade Organization (WTO) and WHO. The debate centres on whether the intellectual property system is: (1) providing sufficient incentives for research and development into medicines for diseases that disproportionately affect developing countries; and (2) restricting access to existing medicines for these countries. The Doha Declaration was adopted at WTO in 2001 and the Commission on Intellectual Property, Innovation and Public Health was established at WHO in 2004, but their respective contributions to tackling intellectual property-related challenges are disputed. Objective parameters are needed to measure whether a particular series of actions, events, decisions or processes contribute to progress in this area. This article proposes six possible benchmarks for intellectual property-related challenges with regard to the development of medicines and ensuring access to medicines in developing countries.